Strengthening the Multiplier Effect Through Local Community Involvement: A Case Study of the Jatiluwih Festival, Bali - Jery Christianto; I Ketut Gunarsa (Jurnal Sains Terapan Pariwisata, 2026)
This study investigates the role of local community participation in enhancing both the economic and cultural impacts of the Jatiluwih Festival. It seeks to understand how engagement in planning, decision-making, and implementation processes can strengthen economic circulation while fostering cultural pride and sustainability. The research adopts a sequential explanatory mixed-methods approach. Quantitative surveys provide insights into local spending patterns and multiplier effects, while qualitative interviews with government officials, private sector representatives, and community members enrich the analysis with perspectives on heritage preservation, product promotion, and social cohesion. Findings demonstrate that community participation significantly amplifies economic benefits for households and microenterprises, particularly in the culinary sector, and reinforces cultural identity. Government support through regulation, infrastructure, and youth training, together with private sector contributions such as sponsorship and digital branding, serve as key catalysts for sustaining competitiveness. Despite limitations in sample size and scope, the research affirms the festival’s potential to be developed as a model for sustainable, culture-based tourism.